Morphological development of sulci in fetal brain: An anatomical study - Sarbani Das; Bal, Kana; Swapan Bhattachrjee (Asian Journal of Medical Sciences, 2022)
Background: The surface of the developing human brain undergoes morphological changes with the formation of different sulci during the fetal period. During the first and second-trimester fetal brain surface remain smooth, and between the 28th and 30th weeks of gestation, new gyri and sulci appear due to rapid growth of the fetal brain. Aims and Objectives: To study the time of appearance of sulci in different surfaces of the fetal brain, which will help estimate the gestational age of the fetus from the specimen of the fetal brain. Materials and Methods: About 108 cerebral hemispheres from 54 fetal brains were examined in the Department of Anatomy, Medical College, Kolkata, West Bengal, in 1 year from December 2016 to December 2017. Among 54 fetal brains, 21 were museum specimens of the Department of Anatomy and Forensic Medicine of Medical College, Kolkata, and the rest were fetal cadavers. For brains from fetal cadavers, after brain removal, it was fixed in 10% formalin. Fetal brains were divided into two groups – a) brains from fetuses with bodyweight up to 1000 g with a weight gap of 100 g among the groups. b) brains from fetuses with body weight >1001 g with a weight gap of 250 g among the groups. Sulci in the superolateral, medial, and inferior surfaces of the fetal brain were noted carefully. Results: Comparing the findings of our study with the previous anatomical studies, it is found that we studied a large number of sulci in detail. When we compared the anatomical findings with the findings of USG or MRI it was found that there was 2–4 weeks delay between anatomical appearance and visualization of the same sulcus in fetal brain by imaging (USG and MRI). The development of cerebral sulci was proportional to the bodyweight of the fetus. Conclusion: Embryological appearance of sulci is a crucial important in the Anatomy and radiological study of brain and micro neurosurgery. The study is essential for estimation of the gestational age of the fetus also.